Diseminasi Teknik Budikdamber Lele untuk Produksi Pangan Skala Rumah Tangga Selama Pandemi Covid-19 - Mojiono Mojiono; Nur Qomariah; Fortunata Riana (Universitas Mathla'ul Anwar Banten, 2020)
CATFISH MINICULTURE OFTEN CALLED AS “BUDIKDAMBER” HAS RAPIDLY GAINED ITS POPULARITY DURING COVID-19 PANDEMIC DUE TO FOLLOWING REASONS: EASY TO ADOPT AND AFFORDABLE. In this regard, we disseminated technical assistance of “budikdamber” to villagers in two villages: Montongsekar and Sugihwaras, which aimed at fostering the food production in households. The dissemination was carried out through three activities: (1) assembly of “budikdamber” unit, (2) assistance and observation, and (3) evaluation. The unit was assembled using 80 L-plastic container, and filled with about 60 L of freshwater. Catfish seeds (12 cm in length) were reared in the unit for 3 weeks. During the period, their growth (body length, in cm) and survival rate. At the end of period, questionnaires were asked to the participants. The results showed that “budikdamber” unit could be made simply, equipped with water outlet, allowing to change water without jeopardizing fish survival. The assistance and observation to the participants demonstrated a pivotal role in disseminating the technical aspects of the catfish miniculture. The aquculture of catfish using “budikdamber” resulted in a satisfying output, represented by high survival rate ranging from 94 - 100% and final fish size (16.82 - 17.90 cm ). For further consideration, we need to publicize the fish culture method using both offline and online approaches, enabling to deliver the benefits of this technique to broader scale. In conclusion, “budikdamber” could impose significant effect on our attempts in ensuring food security during covid-19 pandemic.